2019
DOI: 10.4209/aaqr.2018.08.0322
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sampling Inlet Direction and Distance on Particle Source Measurements for Dispersion Modelling

Abstract: The source rate is the single most critical input parameter in dispersion models. Determining accurate source rates from workplace processes can be challenging due to interference with work operation and poorly known dilution between the outlet of the particle generator and the measurement point. In this work, we measured the aerosol source rate in a chamber with a steady release of TiO 2 particles generated by an aerosol brush generator. The number concentrations measured directly from the particle generator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Because of this limitation, the assessment of the root mean squared logarithmic error (RMSLE) is proposed to not over-penalize differences between predicted and actual values, when concentrations are high [36]. This is because the RMSLE mainly takes into account the ratio of change, rather than the actual concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of this limitation, the assessment of the root mean squared logarithmic error (RMSLE) is proposed to not over-penalize differences between predicted and actual values, when concentrations are high [36]. This is because the RMSLE mainly takes into account the ratio of change, rather than the actual concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…This would mean that, according to the ranges suggested by Jayjock et al (2011), the performance of the one-box model for the industrial scenario assessed in this work would be considered as comparable. In the literature, several authors have reported underestimations by the one-box model [31,35,36,57,58] as it assumes homogeneous concentrations through all the room. This is consistent with our results, even though the high airflows measured in the industrial scenario allowed us to assume adequate mixing, on average.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations